REPERTOIRE DALAM RONGGENG DUKUH PARUK KARYA AHMAD TOHARI KAJIAN ESTETIK WOLFGANG ISER - , inung setyami, Dr. Fadlil Munawwar Manshur, M.S. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The history of modern Indonesian literature development has presented literary pieces linked to social, cultural, and historical facts. It is owing to the fact that the literary pieces cannot be separated from daily lives though the author has transcended his or her social, cultural, and historical facts. Hence, the literary pieces may contain facts despite its fictional status. One of the Indonesian literary pieces representing close relation between social, cultural, and historical facts in the real world and fiction referring to the authorâs imaginative world is Ronggeng Dukuh Paruk by Ahmad Tohari. A research needs to be conducted to see to what extent fiction represents fact. This research entitled âRepertoire in Ahmad Tohariâs Ronggeng Dukuh Paruk: A Study of Wolfgang Iserâs Aestheticâ is aimed at understanding the repertoire in the novel as a background of creation so that foreground the author aspires for couold be revealed. It indirectly suggests a corelation between fact or reality and fiction as Tohariâs imagination as the author of the novel. Applying Wolfgang Iserâs repertoire theory, the research uses the entire texts in the novel trilogy as objects of study. Furthemore, the objects are linked to things that become the basis of creation involving social, cultural, and historical norms found in the text. Having closely read, seeked, and analyzed data, it is revealed that social norms found in the novel refer to social norms within the abangan group of Javanese people which is bounded by the tradition of the believe in foreseeing, inheritage, and magical symbol, unity principle, and their mentality. Dominant culture in the novel is Javanese, that is, Ronggeng art in dealing to the initials of peronggengan or pergowokan. Meanwhile, historical facts as a background of the novel is Ronggeng art found in pre and post the tragedy of G 30S/PKI, which influence the function and the reputation of ronggeng. Through the background and foreground of the authorâs purpose that is socio norms, is brought out to critisize the societyâs condition as mentally and spiritually lived under passive condition. Cultural norm is presented as the shape of disagreement towards the symbol of feodalism of Java people which strongly bounded in the life of the society. Meanwhile, historical norms is used to speak out the intention, such as critics towards the government under strict orde baru regim and which put the art under politics as well.